2011
DOI: 10.1002/lapl.201110012
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Raman scattering in “garnet” Lu3Al5O12 ceramics - a novel host-materiel for Ln- and TM-lasant ions

Abstract: In this paper are present results of the first investigation of stimulated Raman scattering (SRS) in the "garnet" Lu 3 Al 5 O 12 crystalline ceramics, which is promising hostmaterial for activator lasants. With picoseconds laser excitation at 0.53207 μm wavelength was observed and analyzed highorder Stokes and anti-Stokes generation related to two χ (3) -promoting vibration modes (≈ 792 and ≈ 375 cm −1 ) of this novel SRS-active oxide material. A brief review of the pioneering papers on lasers based on Lu3Al5O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Scintillation emission was collected by the same objective and measured by a photo-detector (Micro Photon Devices, SPAD 50 μm, grade C), which also acted as a confocal pinhole. Scattered and reflected excitation and STED photons as well as Raman-scattered STED-laser photons [36][37][38] were blocked by detection optical filters placed in front of the photodetector. The filters were tilted at 10 0 relative to each other and separated by 2 cm to maximize their optical density (OD) at the excitation and STED laser wavelengths.…”
Section: Methodsmentioning
confidence: 99%
“…Scintillation emission was collected by the same objective and measured by a photo-detector (Micro Photon Devices, SPAD 50 μm, grade C), which also acted as a confocal pinhole. Scattered and reflected excitation and STED photons as well as Raman-scattered STED-laser photons [36][37][38] were blocked by detection optical filters placed in front of the photodetector. The filters were tilted at 10 0 relative to each other and separated by 2 cm to maximize their optical density (OD) at the excitation and STED laser wavelengths.…”
Section: Methodsmentioning
confidence: 99%
“…Various rare earth ions doped ceramic laser gain media have been developed and the different laser performances have been demonstrated [19][20][21]. Recently, A.A. Kaminskii et al reported the stimulated Raman scattering in LuAG ceramics and they predicted the future rapid development of the LuAG polycrystalline ceramics as a novel laser gain media [16]. In present work, high optical quality Yb:LuAG laser ceramics have been synthesized by the solid state reactive sintering method under vacuum.…”
Section: +mentioning
confidence: 93%
“…10. The cubic garnet structure of Lu3Al5O12 gives rise to 25 Raman-active modes (irreducible representations: 3A1g + 8Eg + 14F2g) [39]. The most intense band at 374 cm -1 assigned as A1g (FWHM = 11 cm -1 ) is due to the rotation of the [AlO4] tetrahedral unit.…”
Section: Optical Spectroscopymentioning
confidence: 99%